Biophasor: Token supplemented cancellable biometrics - Teoh, Andrew B. J; Ngo, David C. L. (2006)
Biometries characteristics are immutable, resulting in permanent biometrics compromise. To address this problem, we prescribe a generic cancellable biometrics formulation - BioPhasor. BioPhasor is a set of binary code based on iterated mixing between the user-specific tokenised pseudo-random number and the biometric feature. This method enables straightforward revocation of biometric template via token replacement. The transformation is non-invertible and BioPhasor able to achieve extremely low error rate compare to sole biometrics in verification setting. The privacy invasion and nonrevocable problems in biometrics could be resolved by revocation of resulting feature through the pseudo-random number replacement. We also consider an unfavorable scenario in which an imposter has access genuine token and used by the imposter to claim as the genuine user. The feasibility of the formulation is demonstrated by the experiments on fingerprint images from the FVC2004 database.